Direct numerical simulation of turbulent mixed convection of LBE in heated upward pipe flows. (November 2018) - Zhao, Pinghui; Zhu, Jiayin; Ge, Zhihao; Liu, Jiaming; Li, Yuanjie
Highlights: A fully fourth-order DNS code is developed for turbulent mixed convection. The detailed first-order and second-order statistics are given in LBE and air flows. The FIK decomposition is applied to analyze the skin friction and Nusselt number. The quadrant analysis is used to identify the fractional contributions of statistics. Abstract: Turbulent mixed convections of lead-bismuth eutectic in heated upward pipe flows at Re = 2650 are investigated using direct numerical simulation. A high-precision space discretization of fourth-order central scheme is adopted for both velocity advection and diffusion terms. Mean velocity, mean temperature, Reynolds shear stress, heat flux, skin-friction coefficient, Nusselt number and some other statistics are demonstrated. With increasing buoyancy, mean velocity and temperature show a non-monotonic variation trend. Turbulent shear stress, turbulent fluctuation, the skin-friction coefficient, and the Nusselt number all firstly decrease and then increase due to the turbulence attenuation and recovery by buoyancy. The analysis of the turbulent kinetic energy budget shows that the shear stress production is the main source of turbulence recovery in LBE mixed convection, instead of the buoyancy production. The quadrant analysis shows the turbulence recovery is not from the near-wall coherent structures but due to the seriously distorted M -shaped velocity distribution. A new decomposition method shows that the turbulent contribution is important to skin-friction coefficient but is very little to the Nusselt number under present conditions. Therefore, the skin-friction coefficient has a large decrease while the Nusselt number has a slight decrease with increasing buoyancy due to turbulence attenuation.